From Inspiration to Immersion: How Social Media Influencers Shape Travel Intentions Through Enhanced Wellness Awareness - Prabuddha, C.; Dangalla, D.K.T. (Journal of Emerging Management Studies, 2025)
Purpose – This study investigates the influence of Social Media Influencers (SMIs) on travelers’ Intention to Travel (IT) for wellness tourism in Sri Lanka, with a focus on the mediating role of Wellness Tourism Awareness (WTA). The study aims to provide theoretical and practical insights into how influencer-driven content shapes awareness and travel decisions in an emerging wellness tourism market.Design/methodology/approach – A quantitative research design was adopted, collecting data from 384 purposively sampled social media users with prior interest or engagement in wellness tourism. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS to test the hypothesized relationships and the mediating effect of WTA. Reliability, convergent validity, discriminant validity, and mediation were assessed using established criteria (Cronbach’s alpha, CR, AVE, Fornell-Larcker, HTMT, and bootstrapping).Findings – The results demonstrate that SMIs positively influence both IT and WTA, and that WTA positively affects IT. Mediation analysis revealed that WTA partially mediates the SMI–IT relationship, indicating that awareness is a key mechanism through which influencers impact travel intentions, while other factors may also contribute to decision-making.Conclusion – The study confirms that social media influencers play a significant role in enhancing wellness tourism awareness and travel intentions in Sri Lanka. Awareness acts as a partial mediator, highlighting the importance of knowledge acquisition in shaping travel behavior.Implications – Tourism stakeholders can leverage SMIs to design targeted, awareness-driven campaigns that promote Sri Lanka’s unique wellness offerings. The findings provide guidance for selecting appropriate influencer types and content strategies to maximize engagement and conversion among wellness tourists.Originality/value – This study contributes to the literature by empirically examining the mediating role of wellness tourism awareness in the influencer–travel intention relationship within the context of an emerging wellness tourism destination. It bridges a gap in research on digital influencer marketing in tourism and provides a framework for future studies in similar contexts.